AB0795 Hypovitaminosis D and Calcium Intake of Adult Population in Bogota (DICAVITD). (15th July 2016) - Guzman Moreno, R.A.; Piñeros, L.G.; Teheran, A.; Flechas, J.; Mejia, M.
Abstract : Background: The calcium intake on the diet below normal daily requirements is related with low levels of vitamin D. The available scientific evidence supports a key role of calcium and vitamin D in skeletal health. We analyzed this relationship in healthy colombian population and describe this association. Objectives: The main objetive is to Assess the prevalence of hypovitaminosis D and the relationship with the daily calcium intake in a healthy Colombian population. Furthermore it is crucial to estimate the impact of key mineral elements such as Calcium and Vitamin D in bone health. Methods: In a prospective cohort of general population we measure the prevalence of hypovitaminosis D and the calcium intake, (mg/dl) following demographic, antropomethric, biochemical characteristics and sun exposure of the population evaluated. We used a model of multiple regresion to predict the levels of vitamin D regarding the factors analysed. We excluded patients with secondary conditions that affect the absorption of calcium and vitamin D. Results: We included 97 patients, average age 23 yrs, 61% women, average weight 65 kg, Height 165 cm, average BMI 22.8. The calcium intake was 393, 7 mg/d, levels of vitamin D were 23.71. We identified hypovitaminosis D in 87% of the patients, 24.7% had vitamin D defficiency and 63% had insufficiency (Figure 1, Levels of Vitamin D in the population study). The concentration of Vitamin D was calculated in quadratic function, for the relationship between sex, sun exposure and habitual calcium intake. (R:>90%). Conclusions: We found a strong relationship between low calcium intake and hypovitaminosis D in the study group. In a healthy colombian population we saw an important low intake of calcium on the diet and high prevalence of Hypovitaminosis D. These findings have enormous impact on public health policy in our country. Effective and imperative strategies are required to prevent future complications such as Osteoporosis and secondary fractures. References: Catharine-Ross A., et al. The 2011 report on dietary references intake for calcium and vitamin D from the Institute of Medicine. What clinicians need to know. JCEM 2011;96:53–58 Disclosure of Interest: None declared